Clustering Captured Fish Exports with Fuzzy C-Means - Akhmad, Ekka Pujo Ariesanto; Priyono, Budi (Riwayat: Educational Journal of History and Humanities, 2025)
By export destination country group, data on Indonesia's fresh/chilled captured fish exports are collated and tabulated. Nevertheless, export amounts have not been separated in the table of fresh/chilled fish exports. The clustering method will be used to tackle the fresh/chilled fish export data clustering problem. This study is to investigate the use of partition-based clustering, namely Fuzzy C-Means (FCM), to assess export data of caught fish from the primary destination nations using machine learning. The Buletin Statistik Perdagangan Luar Negeri Ekspor Menurut Kelompok Komoditi dan Negara, October 2023 is where the research's data came from. The research variables in this study, which comprise net weight of products (kg) and FOB (free on board) value, are based on data collected between 2022 and 2023. Following a cluster analysis, two clusters are produced: one for high export levels and another for medium or low export levels.